2006
DOI: 10.1021/ac060390t
|View full text |Cite
|
Sign up to set email alerts
|

Microchip-Based Macroporous Silica Sol−Gel Monolith for Efficient Isolation of DNA from Clinical Samples

Abstract: Effective microchip extraction of deoxyribonucleic acid (DNA) from crude biological matrixes has been demonstrated using silica beads or hybrid phases composed of beads and sol-gel. However, the use of monolithic sol-gels alone for extraction of human genomic DNA has been more difficult to define. Here we describe, for the first time, the successful use of monolithic tetramethyl orthosilicate-based sol-gels for effective micro-solid-phase extraction (muSPE) of DNA in a glass microchip format. A functional mono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
82
0
6

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(89 citation statements)
references
References 15 publications
1
82
0
6
Order By: Relevance
“…[12][13][14][15] There have been many reports of lSPE DNA extraction. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Previous reports describe DNA lSPE systems with integrated polymerase chain reaction 21,22 and electrophoretic separation. [23][24][25] Furthermore, DNA lSPE has been applied to forensics, where samples are typically very dilute.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14][15] There have been many reports of lSPE DNA extraction. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Previous reports describe DNA lSPE systems with integrated polymerase chain reaction 21,22 and electrophoretic separation. [23][24][25] Furthermore, DNA lSPE has been applied to forensics, where samples are typically very dilute.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, other phases have been investigated to reduce the non-specific binding of proteins and increase the loading capacity of the solid support. Some examples are monolithic silica phases (Bhattacharyya and Klapperich 2008;Kulinski et al 2009;Wen et al 2007;Wu et al 2006), porous silicon (Chen et al 2008), and chitosan coatings (Hagan et al 2009), which reported for obtaining extraction efficiencies within a range of 70 to 85%. Nevertheless, some preliminary phenol extraction studies using microfluidics have also been conducted by examining organic-aqueous interface stabilization (Reddy and Zahn 2005), experimental and computational evaluation of droplet-based flows (Mao et al 2006), electrohydrodynamic instability (EHD) mixing (Zahn and Reddy 2006), and diffusion limited approaches to protein and DNA partitioning (Morales and Zahn 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The requirement of frits or weirs for the immobilization of particles also increased the difficulty in fabrica-tion. To circumvent this challenge, Wu et al [13] employed a tetramethylortho silicate-based monolith for effective DNA extraction without a frit or weir. Wen et al [14] developed a tetramethyl orthosilicate-grafted monolithic solid-phase in a capillary-based extraction system, which was further modified for microchip-based extraction [15].…”
Section: Introductionmentioning
confidence: 99%